Machine Learning Enhanced Optical Fiber Sensor For Detection Of Glucose Low Concentration In Samples Mimicking Tissue - Babińska, Maria; Władziński, Adam; Talaśka, Tomasz; Szczerska, Małgorzata (Photonics Letters of Poland, 2025)
This study presents an optical fiber sensor for detecting low glucose concentrations in a sample mimicking urine. Our research focused on designing a sensor capable of detecting 0.5% glucose concentrations in artificial urine. Algorithms were applied to analyze and accurately classify the data and identify the principal components of the collected data. The Random Forest and XGBoost model achieved the highest accuracy, confirming that frequency domain analysis combined with machine learning can significantly enhance glucose detection accuracy. These findings demonstrate that integrating machine learning with an optical fiber sensor enables the detection of low glucose concentrations. Full Text: PDF References S. Garcia-Galan, J.A. Cabrera-Rodriguez, F.J. Maldonado-Carrascosa, N. Ruiz-Reyes, M. Szczerska, P. Vera-Candeas, F.D. Gonzalez-Martinez, F.J. Canadas-Quesada, A.J. Cruz-Lendinez, "Expert system against machine learning approaches as a virtual sensor for ventricular arrhythmia risk level estimation", Biomedical Signal Processing and Control 102, 107255 (2025). CrossRef D.D. Nolte, Optical Interferometry for Biology and Medicine (Springer 2012). CrossRef X. Wang, O.S. Wolfbeis, "Fiber-Optic Chemical Sensors and Biosensors (2015–2019)", Anal Chem. 92(1), 397 (2020). CrossRef A. Sękowska, D. Majchrowicz, A. Sabisz, M. Ficek, B. Bułło-Piontecka, M. Kosowska, L. Jing, R. Bogdanowicz, M. Szczerska, "Nanodiamond phantoms mimicking human liver: perspective to calibration of T1 relaxation time in magnetic resonance imaging", Scient. Rep. 10(1), 6446 (2020). CrossRef S. Soria, S. Berneschi, M. Brenci, F. Cosi, G. N. Conti, S. Pelli, G.C. Righini, "Optical Microspherical Resonators for Biomedical Sensing", Sensors 11(1), 785 (2011). CrossRef H. Aouani, F. Deiss, J. Wenger, P. Ferrand, N. Sojic, H. Rigneault, "Optical-fiber-microsphere for remote fluorescence correlation spectroscopy", Opt. Expr. 17(21), 19085 (2009). CrossRef P. Listewnik, M. Bechelany, M. Szczerska, "Microsphere structure application for supercapacitor in situ temperature monitoring", Smart Mat. Struct. 30(10), 10LT01 (2021). CrossRef S.L. Cowart, M.E. Stachura, "Winter Sports Medicine", Jama 264(21), 2808 (1990). CrossRef N. Sarigul, F. Korkmaz, İ. Kurultak, "A New Artificial Urine Protocol to Better Imitate Human Urine", Scient. Rep. 9, 20159 (2019). CrossRef X. Li, Y. Shao, Y. Yu, Y. Zhang, S. Wei, "A Highly Sensitive Fiber-Optic Fabry–Perot Interferometer Based on Internal Reflection Mirrors for Refractive Index Measurement", Sensors 16(6), 794 (2016). CrossRef E. Ujah, M. Lai, G. Slaughter, "Ultrasensitive tapered optical fiber refractive index glucose sensor", Scient. Rep. 13, 4495 (2023). CrossRef M. Grochowski, M. Wąsowicz, A. Mikołajczyk, M. Ficek, M. Kulka, M.S. Wróbel, M. Jędrzejewska-Szczerska, "Machine learning system for automated blood smear analysis", Metrology Measur. Syst. 26(1), 81 (2019). CrossRef I. Feder, M. Wróbel, H. Duadi, M. Jędrzejewska-Szczerska, D. Fixler, "Experimental results of full scattering profile from finger tissue-like phantom", Biomedical Opt. Expr. 7(11), 4695 (2016). CrossRef P. Kluczynski, J. Gustafsson, A.M. Lindberg, O. Axner, "Wavelength modulation absorption spectrometry — an extensive scrutiny of the generation of signals", Science Direct 56(8), 1277 (2001). CrossRef M. Hirsch, D. Majchrowicz, P. Wierzba, M. Weber, M. Bechelany, M. Jędrzejewska-Szczerska, "Low-Coherence Interferometric Fiber-Optic Sensors with Potential Applications as Biosensors", Sensors 17(2), 261 (2017). CrossRef S. Shi, L. Ye, H. Xiao, T. Luo, "A Comparative Study of Mainstream Machine Learning Algorithms for Spine Health Prediction", 16th ICME International Conference on Complex Medical Engineering (CME), pp. 349-355 (2022). CrossRef